An epidemiological study of the prevalence and determinants of overweight and obesity in women of reproductive age (15 to 49 years) group in an urban slum - Mulik, Pratibha U.; Suryawanshi, Sudam R. (International Journal Of Community Medicine And Public Health, 2021)
Background: After comparing data of NFHS-3 and 4, prevalence of overweight and obesity in women of an urban population almost doubled in 10 yr. So, the causes of increasing prevalence need to be studied as public health concern. Objective of the study is to determine prevalence of overweight and obesity among reproductive age group (15-49 years) of women in an urban slum of Mumbai. Methods: Total 220 women were selected among 11 sectors from A to K by simple random method and data collected by using validated questionnaire. WHO’s classification was used to classify as overweight and obese. Results: Out of 220 women participated in study, 14 (6.36%) were obese, 75 (34.09%) were overweight according to BMI and 17 (7.7%) were found to be obese according to waist to hip ratio. From the present study it was seen that age group of the women, socio economic class, education, history of hypothyroidism, family history of obesity, types of work women do, hours of television watching, calorie and fat intake, had a significant relationship with BMI, whereas physical exercise they used to do and tendency to sleep in the afternoon and hours of sleep in the night had non-significant relationship with BMI. Conclusions: Obesity and overweight is found to be a growing public health problem and can be preventable. Interventional measures include developing healthy eating habits, regular moderate physical exercise, sleeping habits, health camps for screening of overweight and obesity.